2012
DOI: 10.1177/0363546512437842
|View full text |Cite
|
Sign up to set email alerts
|

Results of Meniscus Allograft Transplantation Using Bone Fixation

Abstract: Meniscus allograft transplantation using bone fixation resulted in significant symptomatic and functional improvements. Magnetic resonance imaging or second-look arthroscopy was necessary to assess allograft status even after favorable clinical outcome. Meniscus allograft transplantation with bone fixation is considered effective for symptomatic, totally meniscectomized knees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 45 publications
1
104
2
1
Order By: Relevance
“…For this review, 15 studies [4,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] reported their observations from second-look arthroscopies (Tables 1, 2). However, there was no mention of clear recommendations regarding ''when second-look arthroscopy should be performed'' and ''why second-look arthroscopy should be performed.''…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this review, 15 studies [4,6,[9][10][11][12][13][14][15][16][17][18][19][20][21] reported their observations from second-look arthroscopies (Tables 1, 2). However, there was no mention of clear recommendations regarding ''when second-look arthroscopy should be performed'' and ''why second-look arthroscopy should be performed.''…”
Section: Resultsmentioning
confidence: 99%
“…In such instances, MAT is regarded as a promising approach [1,4] for the reconstruction of meniscal biomechanical properties in knees with meniscal deficits and is aided by advanced arthroscopic equipment, instruments, and techniques [25,26]. As the benefits of MAT, including pain relief and functional improvement, have been demonstrated, many methods have been performed to evaluate the clinical outcomes of MAT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, a number of orthopaedic surgeons have reported clinical and radiological mid-term results (Kim et al, 2012;Lee and Caborn, 2012). However, fixation of the allograft, whether soft-tissue or bone plug associated, remains a significant source of failure (Hommen et al, 2007).…”
Section: Meniscal Transplantationmentioning
confidence: 99%